Star of the Sea - O'Connor, Joseph, 1963- (London : Vintage Books, 2005)
On a ship leaving Ireland for America during the Famine, Pius Mulvey, a notorious, sinister criminal, is pressured by a group of fellow steerage passengers to kill the lord who recently evicted them, while Mary, the lord's family nanny and the woman Mulvey abandoned years ago, wonders what his intentions are.
Adult.
Adult
Keywords: Immigrants -- Fiction; Ocean travel -- Fiction; Historical fiction; Immigrants -- Fiction; Mystery fiction; Ocean travel -- Fiction; Ireland -- Emigration and immigration -- Fiction; Ireland -- Immigration and emigration -- Fiction; Historical fiction; Mystery fiction